IDC theory: interest and the interest loop - Wong, Lung Hsiang; Chan, Tak Wai; Chen, Wenli; Looi, Chee Kit; Chen, Zhi Hong; Liao, Calvin C. Y.; King, Ronnel B.; Wong, Su Luan (SpringerOpen, 2020)
Numerous studies have shown that learning is enhanced when students show interest in the subject matter. However, educators continue to grapple with the challenges, or simply do not recognize their potential roles, in the development of students’ academic interest and interest in learning in general. This conceptual paper is written under the auspices of the interest-driven creator (IDC) initiative, a theoretical synthesis effort carried out by a group of educational researchers in Asia. The intention is to co-construct a holistic developmental/design framework to guide the students in fostering their learning interests, capabilities in creation, and learning habits—the three anchored concepts of IDC theory. This paper focuses on delineating a three-component “interest loop” to guide the design of a coherent learning process that encompasses a series of learning tasks. The three components are triggering interest, immersing interest, and extending interest. Underpinned by the rich literature on interest development, we will propose suitable design strategies for each of the three components, namely, curiosity, flow, and meaningfulness, respectively. We will then explicate their respective design considerations/principles to maximize the intended effects.